I Love You I Love You: Aesthetics of love in a culturally diverse youth theatre ensemble. Issue 2 (3rd July 2018) - Woodland, Sarah
ABSTRACT: Although love is rarely addressed in applied theatre and drama scholarship, it is nevertheless often present in participatory theatre practice. The Traction Youth Theatre Ensemble was based in a culturally diverse and vibrant satellite city south of Brisbane, Australia. While I was evaluating Traction's potential to promote social cohesion, I found that feelings and expressions of love informed and formed the aesthetics of the ensemble process, its ritualized daily practices, and its performances. I argue that love deserves our scholarly attention if we are to continue pursuing ideals of social justice in intercultural participatory youth theatre practice and research.